A global enhancement of hydrogen cyanide in the lower stratosphere throughout 2016. Issue 11 (11th June 2017) - Sheese, Patrick E.; Walker, Kaley A.; Boone, Chris D.
Abstract: In September–October 2015, El Niño‐driven weather conditions led to one of the most intense Indonesian peatland burning events in recent history. Consequently, an unprecedented amount of hydrogen cyanide (HCN) was emitted from Southeast Asia and transported into the upper troposphere and lower stratosphere, which was then transported by the general circulation from the tropics to polar latitudes. By early 2016, the daily mean concentrations of HCN in the lower stratosphere at all latitudes, as measured by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE‐FTS) instrument, were the largest on record for the region, on the order of 40–90% greater than the climatological mean and ~40% greater than the 2007 El Niño‐driven values. By December 2016, levels of polar HCN in the lower stratosphere were still on the order 10–20% greater than the climatological mean. These ACE‐FTS measurements are thus vital for interpreting ground‐based and nadir satellite measurements of HCN made during 2016 and could be used to help validate tropospheric‐stratospheric exchange in climate models. Key Points: ACE‐FTS observes extreme concentrations of HCN in lower stratosphere in 2016 HCN concentrations in the lower stratosphere are the largest values on record Enhancements linked to El Niño‐driven high temperatures, drought in Southeast Asia